Reference data for hop tests used in pediatric ACL injury rehabilitation: A cross‐sectional study of healthy children. (22nd May 2021) - Warming, Susan; Alkjær, Tine; Herzog, Robert Bennike; Lundgaard‐Nielsen, Mathilde; Zebis, Mette Kreutzfeldt
Abstract : In rehabilitation, four single‐leg hop tests are frequently used for evaluation of ACL‐injured children. However, reference values on single‐leg hop performance and the corresponding limb symmetry indexes (LSIs) of healthy children younger than 15 years of age are lacking. Thus, the purpose was to describe hop performance and LSIs in healthy Danish children, and to quantify the proportion of participants passing LSI values of ≥85% as well as ≥90%. Healthy children aged 9–15 years were invited to participate in the study. Hop performance (single hop, 6‐m timed hop, triple hop, and cross‐over hop) was assessed for each leg for each hop test and expressed as absolute, normalized (to body height), and LSI values. Descriptive statistics were applied to calculate mean ±SD for all outcomes within age and gender groups. Further, the 95% reference interval was calculated for each age and gender group. A total of 531 healthy children (52% girls) were included in the study, representing seven age groups (9‐15 years). The LSI group means across all participants for the four hop tests ranged between 84 and 95%. Between 70 and 83% of the children had an LSI of ≥85%, while 50 to 65% of the children had an LSI of ≥90%. The present reference material can be used in clinical practice when evaluating hop performance in pediatric ACL patients.